Photovoltaic Solar System for the Residents of Faisalabad: A Cost-Benefit Analysis - Ahmad , Sania; Ahmad, Rashid; Fatima, Sahar; Hussain, Altaf (Pakistan Journal of Humanities and Social Sciences, 2023)
The negative environmental impact of fossil fuels is growing, with the accumulation of the elevation financial charge of energy resources required to meet Pakistan's increasing demand for electricity uses. This study was conducted with the objective to determine the economic viability and feasibility of installing photovoltaic (PV) solar energy in Pakistan. It was discovered that Pakistan’s favorable solar radiation characteristics are crucial for improving the viability of installing solar systems. This study was conducted in an industrial city of Pakistan, Faisalabad. Using the CVM technique primary data on solar PV systems installed in the households was collected. The Cost-Benefit Analysis shows that the true financial cost of a PV module will drastically decrease when the charges of energy assets saved are used in generating conventional electricity.